Estimating age and sex: Paleodemographic identification using rock art hand sprays, an application in Johnson County, Wyoming. (September 2015) - Mackie, Madeline E.
Abstract: Demographics are a common area of study among ethnographic hunter–gatherer populations, but are often neglected archaeologically because of difficulty in directly identifying age and sex from archaeological materials. Hand sprays offer an opportunity to determine the age and sex of rock art creators. Utilizing a series of equations created from an experimental collection of 271 hand sprays of known authorship, the age and sex of individuals responsible for the creation of 78 archaeological hand sprays from three rock art sites located in Johnson County, Wyoming were estimated. The archaeological sprays were measured using three-dimensional models created with close range photogrammetry. Of the total, 49 sprays were sufficiently complete to be identified as children or male or female adults as participants in spray creation. The results suggest that hand sprays were created by children and adults of both sexes suggesting non-exclusivity in activities associated with rock art creation.